SWEARING: FORMS, REFERENTS, FUNCTIONS, AND USERS - Malo, Raynesta Mikaela Indri; Adindarena, Vindya Donna (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
This study attempts to investigate the use of swearing in Waingapu, Indonesia. This is a descriptive study that tries to describe the forms, referents, functions, and users of swearing. Data is collected through recording, questionnaires, and interviews. The finding shows that there are 123 forms of swearing with most swearing referred to parts of the body of 'women' and ‘genitals'. Other referents of swearing are activities, animals, circumstances, objects, kinship, spirts, and profession. Besides, this study becomes proof that swearing is not only used to express anger but also to express other positive feelings. This study also reveals that age, sex, and length of stay do not determine one's knowledge of swearing. However, it reveals that men use swearing more than women.